2013
DOI: 10.3389/fpls.2013.00376
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-based redox signaling in the nitrogen-fixing symbiosis

Abstract: Matamoros have contributed equally to this review.In nitrogen poor soils legumes establish a symbiotic interaction with rhizobia that results in the formation of root nodules. These are unique plant organs where bacteria differentiate into bacteroids, which express the nitrogenase enzyme complex that reduces atmospheric N 2 to ammonia. Nodule metabolism requires a tight control of the concentrations of reactive oxygen and nitrogen species (RONS) so that they can perform useful signaling roles while avoiding ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 85 publications
(126 reference statements)
1
23
0
5
Order By: Relevance
“…Taken together, these results provide further evidence for a functional specialization of these thiols in legumes, although the specific roles of GSH and hGSH in legume nodules are yet to be defined (Frendo et al . ). In the present work, the decline in GSH can only be partially attributed to direct antioxidant functions since the levels of the oxidized form, GSSG, remained relatively constant during the experiment (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Taken together, these results provide further evidence for a functional specialization of these thiols in legumes, although the specific roles of GSH and hGSH in legume nodules are yet to be defined (Frendo et al . ). In the present work, the decline in GSH can only be partially attributed to direct antioxidant functions since the levels of the oxidized form, GSSG, remained relatively constant during the experiment (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, these two spots consisted of proteins containing cysteine residues reduced by PBZ treatment. Mass spectrometry analysis revealed that Spot 10 contained O.sativa thioredoxin (OsTRXh1), a ubiquitous redox protein that exhibits disulfide oxidoreductase activity through the reversible oxidation of two cysteine residues in a CXXC motif to a disulfide [28, 29], whereas Spot 11 contained OsRACK1A, which was detected as an oxidized protein in cultured cells expressing DN-OsRac1 (Table 1). Taken together, we identified seven potential redox proteins.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In this context, several studies demonstrated the importance of sulfate uptake and metabolism for the establishment and function of SNF (Matamoros et al, 1999(Matamoros et al, , 2003Abbas et al, 2002;Harrison et al, 2005;Krusell et al, 2005;Bianucci et al, 2008;Muglia et al, 2008;Chang et al, 2009;Becana et al, 2010;El Msehli et al, 2011;Frendo et al, 2013). However, little is known about the molecular and biochemical mechanisms governing S-reduction and metabolism during SNF and the impact of nodulation on the whole-plant S-metabolism.…”
Section: Discussionmentioning
confidence: 99%